(untitled) (Journal of Parents and Teachers, 2026)
When someone in the family has Alzheimer’s, there are some essential premises, many of which are perhaps debatable. First, the whole family suffers from the disease, especially those who care for the patient minute by minute. Those who suffer from it suffer less and less, while those who accompany them suffer more and more. Secondly, there is no cure, only ways to improve quality of life. It is very important that carers know how to be, how to act and how to behave, as well as being mature. On the other hand, carers must take care of themselves, find time for themselves, to rest and relax, as well as support from other people.